Uji Aktivitas Antibakteri Serum Ekstrak Etanol 70% Daun Turi Putih (Sesbania grandiflora L) Terhadap Bakteri Staphylococcus Aureus - Dita Purnama; Gigih Kenanga Sari; Maulita Saraswati (Pratama Medika : Jurnal Kesehatan, 2024)
White turi is a plant that contains active substances that act as antibacterials, including saponins, flavonoids and tannins which can inhibit the growth of Staphylococcus aureus bacteria. Currently, the use of natural ingredients in cosmetic preparations has been developed. One of the cosmetic preparations that has developed recently is serum. This study aims to determine the antibacterial activity of serum 70% ethanol extract of white turi leaves (Sesbania grandiflora L) against Staphylococcus aureus bacteria. This research method is experimental research. White turi leaves were extracted using the maceration method with 70% ethanol solvent. The 70% ethanol extract of white turi leaves was made into serum with a concentration of 2%, 4%, 8% and the physical quality was evaluated including organoleptic tests, homogeneity, pH, spreadability, viscosity and the antibacterial activity of the serum was tested using the paper disk diffusion method. The results of the research on the formulation of the serum preparation are brownish yellow in color, have a distinctive odor of 70% ethanol extract of white turi leaves and are slightly thick, homogeneous, with a pH value = 5.65-5.86, spreadability = 5.3-6.33, viscosity = 341.66-466.46 and the inhibition zone for antibacterial activity of formula 1 is 9.48 mm (medium), formula 2 is 12.50 mm (strong) and formula 3 is 14.46 mm (strong). Based on the results obtained, it can be concluded that all serum formulas of 70% ethanol extract of white turi leaves can inhibit the growth of Staphylococcus aureus bacteria in the medium-strong category and the serum formula of 70% ethanol extract of white turi leaves (Sesbania grandiflora L) has the best activity on growth. Staphylococcus aureus bacteria is formula 3 with a concentration of 8% with an inhibition zone of 14.46 mm (strong).